Comparative Genomics Analysis of a New Exiguobacterium Strain from Salar de Huasco Reveals a Repertoire of Stress-Related Genes and Arsenic Resistance - Castro-Severyn, Juan; Remonsellez, Francisco; Valenzuela, Sandro L.; Salinas, Cesar; Fortt, Jonathan; Aguilar, Pablo; Pardo-Esté, Coral; Dorador, Cristina; Quatrini, Raquel; Molina, Franck; Aguayo, Daniel; Castro-Nallar, Eduardo; et al. (Frontiers in Microbiology, 2017)
The Atacama Desert hosts diverse ecosystems including salt flats and shallow Andean lakes. Several heavy metals are found in the Atacama Desert, and microorganisms growing in this environment show varying levels of resistance/tolerance to copper, tellurium, and arsenic, among others. Herein, we report the genome sequence and comparative genomic analysis of a new Exiguobacterium strain, sp. SH31, isolated from an altiplanic shallow athalassohaline lake. Exiguobacterium sp. SH31 belongs to the phylogenetic Group II and its closest relative is Exiguobacterium sp. S17, isolated from the Argentinian Altiplano (95% average nucleotide identity). Strain SH31 encodes a wide repertoire of proteins required for cadmium, copper, mercury, tellurium, chromium, and arsenic resistance. Of the 34 Exiguobacterium genomes that were inspected, only isolates SH31 and S17 encode the arsenic efflux pump Acr3. Strain SH31 was able to grow in up to 10 mM arsenite and 100 mM arsenate, indicating that it is arsenic resistant. Further, expression of the ars operon and acr3 was strongly induced in response to both toxics, suggesting that the arsenic efflux pump Acr3 mediates arsenic resistance in Exiguobacterium sp. SH31.